Effect of Maxigrain Supplementation of Diets with or Without Rice Offal on the Performance of Broiler Chicks - Duru, S.; Dafwang, I.I. (International Journal of Poultry Science, 2010)
Three experiments were conducted concurrently to determine the effect of maxigrain supplementation of isocaloric diets with or without rice offal, the effect of maxigrain supplementation of diets containing rice offal at two levels of energy and the effect of maxigrain supplementation of diets in which the maize content was substituted with rice offal on a weight to weight basis. The experiments were conducted with 210 broilers from 2-5 weeks of age. Results showed that maxigrain supplementation did not have any effect on broiler performance when broilers were fed isocaloric and isonitrogenous diets with or without rice offal. Maxigrain supplementation improved the performance of broilers when added to low energy diets. The improvement in broiler performance was same at 0.1 and 0.2% maxigrain supplementation. The study confirmed earlier recommendations that rice offal can be fed at levels of up to 15% in broiler chick diets without adverse effect on growth performance and concluded that maxigrain enzyme supplementation may be beneficial only when added to diets containing lower than recommended energy and protein levels.